Low Levels of Physical Activity During Critical Illness and Weaning: The Evidence–Reality Gap. (October 2019) - Connolly, Bronwen A.; Mortimore, Jessica L.; Douiri, Abdel; Rose, Joleen W.; Hart, Nicholas; Berney, Susan C.
Background: Physical rehabilitation can benefit critically ill patients during intensive care unit (ICU) admission, but routine clinical practice remains inconsistent nor examined in prolonged mechanical ventilation patients transferred to a specialist ventilator weaning unit (VWU). Behavioral mapping is a sampling approach that allows detailed reporting of physical activity profiles. The objective of this study was to characterize the physical activity profile of critically ill patients in a UK ICU and VWU. Methods: Single-center, prospective observational study in a university teaching hospital. Patient observations, conducted Monday through Sunday from 08:30am to 08:00pm and for 1 minute every 10 minutes, included data points of patient location, people in attendance, and highest level of activity. Descriptive statistics were utilized to analyze and report data. Results: Forty-two ICU and 11 VWU patients were recruited, with 2646 and 693 observations, respectively, recorded. In the ICU, patients spent a median (interquartile range) of 100% (96%-100%) of the day (10.5 [10.0-10.5] hours) located in bed, with minimal/no activity for 99% (96%-100%) of the day (10.4 [9.7-10.5] hours). Nursing staff were most frequently observed in attendance with patients irrespective of ventilation or sedation status, although patients still spent approximately two-thirds of the day alone. Bed-to-chair transfer was the highest activity level observed. In the VWU, patients spent 94% (73%-100%) of the day (9.9 [7.7-10.5] hours) in bed and 56% (43%-60%) of time alone. Physical activity levels were higher and included ambulation. All physical activities occurred during physical rehabilitation sessions. Conclusions: These profiles of low physical activity behavior across both patients in the ICU and VWU highlight the need for targeted strategies to improve levels beyond therapeutic rehabilitation and support for a culture shift toward providing patients with, and engaging them in, a multidisciplinary, multiprofessional environment that optimizes overall physical activity.